Voltammetric Determination of Homocysteine Using Multiwall Carbon Nanotube Paste Electrode in the Presence of Chlorpromazine as a Mediator - Fathali Gholami-Orimi; Farshad Taleshi; Pourya Biparva; Hassan Karimi-Maleh; Hadi Beitollahi; Hamid R. Ebrahimi; Mohamad Shamshiri; Hasan Bagheri; Masoud Fouladgar; Ali Taherkhani (Journal of Analytical Methods in Chemistry)
We propose chlorpromazine (CHP) as a new mediator for the rapid, sensitive, and highly selective voltammetric determination of homocysteine (Hcy) using multiwall carbon nanotube paste electrode (MWCNTPE). The experimental results showed that the carbon nanotube paste electrode has a highly electrocatalytic activity for the oxidation of Hcy in the presence of CHP as a mediator. Cyclic voltammetry, double potential step chronoamperometry, and square wave voltammetry (SWV) are used to investigate the suitability of CHP at the surface of MWCNTPE as a mediator for the electrocatalytic oxidation of Hcy in aqueous solutions. The kinetic parameters of the system, including electron transfer coefficient, and catalytic rate constant were also determined using the electrochemical approaches. In addition, SWV was used for quantitative analysis. SWV showed wide linear dynamic range (0.1–210.0 μM Hcy) with a detection limit of 0.08 μM Hcy. Finally, this method was also examined as a selective, simple, and precise electrochemical sensor for the determination of Hcy in real samples.